An Examination of Translated Works from English to National Languages in Kabul Universities during (2019-2020): Translation - Abdul Rahman Nahza; Sayed Azimullah Esmati; Mohammad Sadiq Esar (CV. AFDIFAL MAJU BERKAH, 2024)
This research employs an analytical-statistical approach to investigate the extent of translation utilization in four universities located in Kabul, Afghanistan. This research has been initiated across 96 academic disciplines in 25 public universities in Afghanistan The study aims to illustrate the landscape of translation activities during the academic year (2019-2020) and assess the progress made in comparison to preceding years. The research findings reveal a noteworthy increase in the number of subject registrations for translation in the four prominent Kabul universities, demonstrating an approximate 30% difference between the academic year 1398 and its antecedent. While the overall quantity of translated works may not be exceptionally high, it signifies a positive and significant stride toward augmenting materials and resources for academic research in the country. The primary focus of inquiry was on establishing an effective translation process within Afghan universities to leverage the works and research conducted by scholars from other nations. The unprecedented resurgence observed in the academic year 1398 in Kabul universities stands in stark contrast to the academic landscape of the 1990s.